The people named the Chippewa : narrative histories - Vizenor, Gerald Robert, 1934- (University of Minnesota Press, 1984)
Ranging in time and space from Madeline Island and the reservations of northern Minnesota to the urban reservation of Minneapolis-St. Paul, Vizenor recounts the experiences of the Chippewa and their encounters with the white people who "named" them